How Strong Are Bequest Motives? Evidence Based on Estimates of the Demand for Life Insurance and Annuities - Bernheim, B. Douglas (Journal of Political Economy, 1991)
This paper presents new empirical evidence in support of the view that a significant fraction of total saving is motivated by the desire to leave bequests. Specifically, the author finds that social security annuity benefits significantly raise life insurance holdings and depress private annuity holdings among elderly individuals. These patterns indicate that the typical household would choose to maintain a positive fraction of its resources in bequeathable forms, even if insurance markets were perfect. Evidence on the relationship between insurance purchases and total resources reinforces this conclusion. Copyright 1991 by University of Chicago Press.